The Moderating Roles of Involvement and Heuristics on Advertising Effectiveness: A Study of Financial Advertisements - Wu, Wann-Yih; Lu, Hsiao-Yun; Chen, Liang-Tzu (Asian Journal of Business and Accounting, 2017)
This study investigates the effect of advertisement appeals and the moderating effects of involvement and heuristics of 50 financial advertisements on consumers’ emotional/cognitive responses, attitude and purchase intention in Taiwan. The findings indicate that consumers tend to process their emotional responses first, followed by their cognitive ones when emotional appeals are dominant. However, the process is reversed when the cognitive messages are dominant. Between the two advertising approaches, emotional appeal is identified to produce greater explained variance in the advertising effectiveness. The findings also suggest that involvement can serve as a moderator to accelerate the influence of advertising appeal on consumer responses. Keywords: Advertising Appeal, Attitude, Heuristics, Involvement, Response